The role of anger and depressive mood in transformation process from victimization to perpetration. (January 2017) - Lee, Yanghee; Kim, Sangwon
Abstract: Violence exerts detrimental influence on children's lives. Reported delinquent behaviors of children have reached an alarming level throughout all societies, and tend to be followed by further victimization. Victimized children suffer various physical and psychological difficulties, with the worst being further involved in perpetrations which puts these children at a greater risk. This study explores the transformation process from victimization to perpetration, by hypothesizing that depressive mood and anger serve as mediators. Data extracted from the Korean Child Youth Panel Survey (KCYPS), of which the first wave (8th graders, n = 2283) were used. Apart from depressive mood and anger, we included violent parenting and peer victimization to measure victimization, and for perpetration, conventional and cyber delinquent behaviors were s included in this model. Structural Equation Modeling was employed to test the hypothesis using Mplus, and bootstrapping method was used to test mediators while FIML was used to handle missing responses. The model yielded an appropriate fit including chi-square = 391.477 (df = 73, p <  0.001), CFI = 0.968, TLI = 0.954, RMSEA = 0.044 (0.040–0.048). Specifically, anger was reported to be mediated in the relations between victimization and perpetration. Depressive mood was mediated in the relations between victimization and perpetration, except for the relation arising from parental victimization. The implications of these findings related to the transformation process and future research direction are discussed.